Stability of antioxidant compounds and activities of a natural dye from coloured-flesh potatoes in dairy foods. (June 2021) - Tereucan, Gonzalo; Ercoli, Stefano; Cornejo, Pablo; Winterhalter, Peter; Contreras, Boris; Ruiz, Antonieta
Abstract: The use of natural dyes such as anthocyanins in foods has disadvantages due to their relatively high costs and low stability. Striking advantages, however, include natural origins and favourable bioactivities. Therefore, the use of a pigment extract from coloured-flesh potatoes is proposed here as a natural dye in dairy foods. The phenolic compound composition, antioxidant activities, and sensorial parameters under different storage conditions were evaluated. In milk stored at room temperature (20 °C) and yogurt, a decrease between 26% and 32% in anthocyanin concentrations was observed after eight weeks, whereas in cooled milk (4 °C), the pigments were stable throughout the same storage time. Similar tendencies were observed between total phenolic compounds and antioxidant activities in milk and yogurt, suggesting that other phenolic compounds contained in dairy foods and potato extract are also affected by storage conditions. In the case of yogurt, the addition of the potato pigment extract did not affect the organoleptic properties. Based on these results, phenolic extracts from coloured-flesh potatoes are an optimal natural and stable alternative for colouring dairy food products, which also provides added value through the addition of biologically active anthocyanins. Highlights: An extract from purple flesh-coloured potatoes was used as natural dye in dairy foods. Anthocyanins from extract were stable during a time similar to commercial storage. Cooled storage conditions showed high stability of purple potato dyes in dairy foods. Flesh-coloured potato extract represent a natural dye with high functional properties.